1996
DOI: 10.3147/jsfp.31.145
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Marine Birnaviruses Isolated from Turbot(Scophthalmus maximus).

Abstract: Six marine birnaviruses isolated from turbot (Scophthalmus maximus) were compared with the infectious pancreatic necrosis virus reference strains Sp, Ab and WB from salmonid fish. This comparison was carried out by PAGE analysis of viral RNA and polypeptides and comparison of the reaction pattern with 4 monoclonal antibodies against the reference strains. High heterogeneity was found among the 6 isolates when comparing the RNA and polypeptide electrophoretic patterns and their reactions with the monoclonal ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
0
8
1
Order By: Relevance
“…MABV Y-6 was also homologous with other MABV isolates from several marine fish in Japan (Kusuda et al, 1993). Therefore, birnavirus from various marine fish in coastal areas of Korea and Japan are serologically homologous, in contrast to other studies in Europe (Novoa and Figueras, 1996;Cutrin et al, 2000). Nishizawa et al (2005) also suggested that aquabirnavirus isolated from marine fish in Japan were indigenous to Japan, based on a phylogenetic analysis.…”
Section: Nc1mentioning
confidence: 80%
See 1 more Smart Citation
“…MABV Y-6 was also homologous with other MABV isolates from several marine fish in Japan (Kusuda et al, 1993). Therefore, birnavirus from various marine fish in coastal areas of Korea and Japan are serologically homologous, in contrast to other studies in Europe (Novoa and Figueras, 1996;Cutrin et al, 2000). Nishizawa et al (2005) also suggested that aquabirnavirus isolated from marine fish in Japan were indigenous to Japan, based on a phylogenetic analysis.…”
Section: Nc1mentioning
confidence: 80%
“…The results indicate that these isolates are serologically homologous. Novoa and Figueras (1996) reported that six marine birnaviruses isolated from turbot Scophthalmus maximus in a restricted geographic area off the coast of Galicia (northwestern Spain) revealed a high heterogeneity of nucleotide sequences and polypeptide electrophoretic patterns and their reactions with the monoclonal antibodies. In addition, the turbot isolates were not exactly the same as the reference strains of IPNV Ab, Sp, and VR-299.…”
Section: Nc1mentioning
confidence: 99%
“…Virus. Four reference strains of birnaviruses (Sp, Ab, WB, and the Norwegian serotype N1) and six birnaviruses isolated from turbot (306, 311, 390, 231, 160, and 460) were used (21). Stock viruses were prepared in the CHSE-214 cell line derived from chinook salmon (17).…”
Section: Methodsmentioning
confidence: 99%
“…The main properties of these MAbs are summarized in Table 1. The immunodot assay was performed as previously described (21). Briefly, the viruses, with a minimum titer of 10 7 50% tissue culture infective doses per ml were added to a hydrated nitrocellulose membrane in a Multiwell BioDot system (Bio-Rad) and incubated for 1 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation